Synthesis of a sulfur-graphene composite as an enhanced metal-free photocatalyst - Peng, Wenchao; Li, Xiaoyan (Nano research, 2013)
A novel metal-free photocatalyst--sulfur/graphene （S/GR） composite--has been synthesized using a facile one-pot, two-step hydrothermal method with thiosulfate and graphene oxide （GO） as precursors. A green reductant--L-ascorbic add--was used to transform GO to GR under mild conditions. The photocatalyst powders were characterized by Fourier transform infrared spectroscop, X-ray diffraction, transmission electron microscopy, scanning electron microscopy, and energy dispersive spectroscopy. Experimental tests were conducted on the photocatalytic decomposition of methyl orange （MO） by different catalysts. Compared to pure oL-S, the as-prepared S/GR composite showed much enhanced photocatalytic activity for the degradation of MO under both UV and solar light. The presence of GR also greatly increased the hydrophilicity and adsorption capacity of the catalyst material. The results indicate that the incorporation of GR with a-S results in a synergistic effect for the S-based photocatalysts offering more effective environmental applications.